Brushed nasal epithelial cells are a surrogate for bronchial epithelial CFTR studies - Brewington, John J.; Filbrandt, Erin T.; LaRosa, F.J.; Moncivaiz, Jessica D.; Ostmann, Alicia J.; Strecker, Lauren M.; Clancy, John P. (JCI insight, 2018)
Recent advances in the management of cystic fibrosis (CF) target underlying defects in the CF transmembrane conductance regulator (CFTR) protein, but efficacy analyses remain limited to specific genotype-based subgroups. Patient-derived model systems may therefore aid in expanding access to these drugs. Brushed human nasal epithelial cells (HNEs) are an attractive tissue source, but it remains unclear how faithfully they recapitulate human bronchial epithelial cell (HBE) CFTR activity. We examined this gap using paired, brushed HNE/HBE samples from pediatric CF subjects with a wide variety of CFTR mutations cultured at the air-liquid interface. Growth and structural characteristics for the two cell types were similar, including differentiation into mature respiratory epithelia. In electrophysiologic analysis, no correlation was identified between nasal and bronchial cultures in baseline resistance or epithelial sodium channel (ENaC) activity. Conversely, robust correlation was demonstrated between nasal and bronchial cultures in both stimulated and inhibited CFTR activity. There was close correlation in modulator-induced change in CFTR activity, and CFTR activity in both cell types correlated with in vivo sweat chloride measurements. These data confirm that brushed HNE cell cultures recapitulate the functional CFTR characteristics of HBEs with fidelity and are therefore an appropriate noninvasive HBE surrogate for individualized CFTR analysis.